PELATIHAN DAN PEMBANGUNAN HYBRIDISASI PLT MIKROHYDRO–PLT SOLAR POWER DI GEREJA KATOLIK ST.ANNA LEKKE KEC. SIMBUANG KABUPATEN TANA TORAJA - Aries Kamolan; Syahir Mahmud; Limbran Sampebatu (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Currently, people at Lekke Village use electricity supplied by Micro hydro Power Plant. The plant of this turbine is located at about 5-6 km from the village and operates only about 10-12 hours per day, from 06.00 PM in evening to 06.00 AM in the morning. The remote location of the micro hydro plant decreases the received voltage at the community. Besides, the unstable condition of turbine installed at Lekke Village resulted in the fluctuation of the output frequency and voltage.  At dry season, the decrement of water flow makes the decrement of the supplied power from the micro hydro plant. While in rainy season, the turbine sometimes fail to operate properly because of garbage, dry leaves, etc. which fall into the river and blocked its flow. Due to this condition, the needs of electricity at Lekke Village are crucial and needs the installation of solar power to meet the community needs. This activity trains local people to have a basic ability on how to build hybrid power installation of turbine and solar power. For this purpose Pengabdian Kepada Masyarakat (PKM) Team from Enginering Faculty of Atmajaya Makassar University is funded by Dirjen Pendidikan Tinggi, Riset dan Teknologi Kementerian Pendidikan dan Kebudayaan through Kegiatan Bantuan Pendanaan Program Penelitian Kebijakan Merdeka Belajar Kampus Merdeka dan Pengabdian Masyarakat Berbasis Hasil Penelitian dan Purwarupa PTS Ditjen Diktiristek.  This training provides 2 basic skills to local people: 1). How to install Solar Power to be used at Sound System and lighting in the St.Anna church; 2) How to build the control system for the hybridization of micro hydro power-solar power.  This training conducts in 2 consecutive session which is training session and installation session. Training session provide basic knowledge of micro hydro power-solar power to the local people and at the installation session the local people together with the trainer work together to install the solar power at St. Anna Church. This activity installs 2X140 WP solar panel with capacity equal to 140 Watt. The solar panel supported by 2x60 Watt batteries. After the installation, the installed system at St.Anna Church able to work 24 hours, supply 70 Watt Sound System and activate 10 lighting points where each point needs 7 Watt. The hybrid installation equipped with a controller that gives ability to select the input power from micro hydro power or from solar power